Pengaruh Pembelajaran Berbasis Proyek Terhadap Kemampuan Kewirausahaan Siswa Kelas XII MAN 5 Jombang - Naila Rahmawati; Sabila Khansa Aulia (Educational Note, 2025)
Instilling Entrepreneurial Spirit Among Students is a crucial aspect in preparing a young generation that is independent, creative, and competitive in the global era. This study aims to analyze the effect of Project-Based Learning (PjBL) on the entrepreneurial skills of 12th-grade students at MAN 5 Jombang. A quantitative approach with a quasi-experimental method was employed in this study, using a pretest-posttest control group design. The research sample consisted of 60 students divided into an experimental group and a control group. The research instrument was an entrepreneurial skill questionnaire covering aspects such as creativity, innovation, risk-taking, as well as the ability to design and run a business. Data analysis using a t-test revealed a significant difference between the experimental and control groups (p < 0.05), with the group receiving project-based learning showing greater improvement in entrepreneurial skills. These findings indicate that the PjBL model is effective in fostering students' entrepreneurial attitudes and skills, as it encourages active engagement, real-world problem-solving, and the development of business ideas. Therefore, implementing project-based learning can serve as an alternative learning strategy in madrasahs to support character education and 21st-century skills development. Recommendations are addressed to teachers and educational policymakers to sustainably integrate this approach into the entrepreneurship curriculum.